Efficacy and Safety of Tumor Treating Fields (TTFields) in Elderly Patients with Newly Diagnosed Glioblastoma: Subgroup Analysis of the Phase 3 EF-14 Clinical Trial - Ram, Zvi; Kim, Chae-Yong; Hottinger, Andreas F.; Idbaih, Ahmed; Nicholas, Garth; Zhu, Jay-Jiguang (Frontiers in Oncology, 2021)
Background: Understudied elderly patients comprise a large segment of high-risk patients with glioblastoma (GBM) that are challenging to treat. Tumor Treating Fields (TTFields) is a loco-regional, non-invasive, antimitotic therapy delivering low-intensity, intermediate-frequency alternating electric fields to the tumor. In the phase 3 EF-14 clinical trial, TTFields (200 kHz) improved median progression-free survival (PFS) and median overall survival (OS) in patients with newly-diagnosed GBM (ndGBM) when added concomitantly to maintenance temozolomide (TMZ). This EF-14 subgroup analysis evaluated the safety and efficacy of TTFields in elderly patients. Methods: All 134 patients who are ≥65 years of age were included (TTFields/TMZ combination, n=89; TMZ monotherapy, n=45; 2:1 ratio of randomization). PFS and OS were analyzed using Kaplan–Meier methodology (α=0.05). Health-related quality-of-life (HRQoL) was assessed using the European Organisation for Research and Treatment of Cancer (EORTC) quality-of-life questionnaire QLQ-C30 supplemented with the brain tumor module (QLQ-BN20). Adverse events (AEs) were evaluated using Common Terminology Criteria for AEs (CTCAE) v4.0. Results: PFS was 6.5 months in patients in the TTFields/TMZ combination group versus 3.9 months in patients treated with TMZ monotherapy (HR, 0.47; 95%CI, 0.30–0.74; P<0.0236). OS was 17.4 months in patients treated with TTFields/TMZ combination versus 13.7 months in patients treated with TMZ monotherapy (HR, 0.51; 95%CI, 0.33–0.77; P<0.0204). Annual survival rates with TTFields/TMZ versus TMZ monotherapy were 39% (95%CI, 29–50%) versus 27% (95%CI, 15–41%; P=0.072) at 2 years, 19% (95%CI, 11–29%) versus 11% (95%CI, 4–23%; P=0.135) at 3 years, and 15% (95%CI, 7–25%) versus 0% at 5 years, respectively. There were no significant differences between groups in the pre-selected items of HRQoL assessment. Grade ≥3 systemic AEs were 46% in the TTFields/TMZ group versus 40% in the TMZ group, without statistically significant difference between the two groups. The only TTFields-related AEs were reversible scalp skin reactions, with grades 1–2 and grade 3 skin reactions reported by 51% and 2% of patients, respectively. Conclusions: Combining TTFields with maintenance TMZ significantly improved PFS and OS in elderly patients with ndGBM in the phase 3 EF-14 clinical trial, without significant increases in systemic toxicity or negatively affecting patients HRQoL. TTFields-related skin AEs were low-grade and manageable.